INTEGRATING DATA-DRIVEN MANAGEMENT AND PHYTOREMEDIATION FOR SUSTAINABLE PETROCHEMICAL WASTEWATER TREATMENT IN BALIKPAPAN - Merry Krisdawati Sipahutar (Institut Teknologi Nasional, Bandung, 2026)
Rapid industrialization in Balikpapan, East Kalimantan, Indonesia, has intensified petrochemical wastewater generation, contributing to persistent aquatic pollution. This study integrates data-driven management with phytoremediation to develop a sustainable framework for hazardous waste mitigation in industrial corridors. Through systematic data collection and descriptive analysis, key operational factors influencing waste intensity were identified, including production throughput, chemical feedstock use, and treatment system age as key determinants of waste intensity. Concurrently, a constructed wetland experiment assessed three macrophyte species (Eichhornia crassipes, Phragmites australis, and Typha latifolia) with and without rhizobacterial augmentation (Pseudomonas fluorescens MC46 and Sphingobacterium sp. MC43). After 60 days, Typha latifolia achieved the highest removal of BPA (79%), parabens (73%), Pb (83%), Cr (76%), and Ni (74%), while Eichhornia achieved the greatest reductions in COD (71%), BOD (68%), and TPH (68%). Rhizobacterial inoculation enhanced degradation by up to 25% through enzymatic biotransformation and biofilm formation. Integrating predictive analytics with experimental outcomes produced the Integrated Waste Management-Phytoremediation Framework (IWM-PF), which improved compliance (+33%), reduced pollutants (-74% COD; -76% metals), and enhanced circular economy integration (+2%). The IWM-PF presents a replicable, data-informed model for industrial wastewater governance aligned with Sustainable Development Goal (SDG) 6-Clean Water and Sanitation, fostering sustainable industrial transformation in Balikpapan.